2022
DOI: 10.1002/jgh3.12852
|View full text |Cite
|
Sign up to set email alerts
|

Vonoprazan and high‐dose amoxicillin dual therapy for Helicobacter pylori first‐line eradication: A single‐arm, interventional study

Abstract: Background: To date, no interventional trial has assessed the efficacy and safety of vonoprazan and high-dose (500 mg four times daily, 2000 mg/day) amoxicillin dual therapy in terms of Helicobacter pylori eradication. We explored whether this was an appropriate first-line treatment. Methods: This prospective, dual-center, single-arm interventional study was performed in Japan. Twenty H. pylori-positive patients lacking any eradication history were treated with vonoprazan 20 mg twice daily and amoxicillin 500 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…Of the 18 included studies, there were 14 RCTs, 9,14,[21][22][23][24][25][26][27][28][29][30]32,33 3 observational studies, 12,13,20 and 1 single-arm study. 31 In these studies overall, I 2 = 91.3%, p < 0.0001; Figure S2) with 1000 mg tid and 750 mg qid, respectively.…”
Section: Study Selection and Characteristicsmentioning
confidence: 75%
See 2 more Smart Citations
“…Of the 18 included studies, there were 14 RCTs, 9,14,[21][22][23][24][25][26][27][28][29][30]32,33 3 observational studies, 12,13,20 and 1 single-arm study. 31 In these studies overall, I 2 = 91.3%, p < 0.0001; Figure S2) with 1000 mg tid and 750 mg qid, respectively.…”
Section: Study Selection and Characteristicsmentioning
confidence: 75%
“…Figure 1 presents detailed reasons for exclusion. Of the 18 studies included, 11 studies 9,13,20,21,[23][24][25][26][29][30][31] analyzed the eradication effects of VLA dual therapies, and VHA dual therapies were also reported by 11studies. 9,12,14,[22][23][24][25]27,28,32,33 As shown in Table 1, the characteristics of the 18 included studies are summarized.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher eradication rate (94.4% in PP analysis) of 7‐days VA was reported by a retrospectively study, 19 amoxicillin was used 500 mg three times daily. The efficacy of vonoprazan with high‐dose (500 mg four times daily, 2000 mg/day) amoxicillin dual therapy for 7 days was also evaluated in Japan and the eradication rate was reported as 94.4% 20 . However, the sample size of this study was limited.…”
Section: Discussionmentioning
confidence: 95%
“…The efficacy of vonoprazan with high-dose (500 mg four times daily, 2000 mg/day) amoxicillin dual therapy for 7 days was also evaluated in Japan and the eradication rate was reported as 94.4%. 20 However, the sample size of this study was limited. We reported that vonoprazan with 2 g daily or 3 g daily amoxicillin for 7 days and showed unacceptable low efficacy in China, 21 which was further confirmed by a multicenter study.…”
Section: Discussionmentioning
confidence: 96%